Cardiovascular health metrics, muscle mass and function among Italian community-dwellers: the Lookup 7+ project. (14th March 2018) - Landi, Francesco; Calvani, Riccardo; Picca, Anna; Tosato, Matteo; Martone, Anna Maria; Ortolani, Elena; Salini, Sara; Pafundi, Teodosio; Savera, Giulia; Pantanelli, Cecilia; Bernabei, Roberto; Marzetti, Emanuele
Abstract: Background: Primordial prevention is essential for promoting cardiovascular health and longevity through the so-called seven cardiovascular health metrics (CHMs) (i.e. smoking, body mass index, diet, physical activity, blood pressure, blood glucose and total cholesterol). Measures of muscle mass and function are recognized as powerful predictors of health-related events and survival. Therefore, the present study was undertaken to assess the prevalence and distribution of the seven CHMs and measures of muscle mass and function in an unselected cohort of community-dwellers. Methods: The Longevity check-up 7+ (Lookup 7+) project is an ongoing cross-sectional survey conducted in unconventional settings (e.g. exhibitions, malls and health promotion campaigns) across Italy. CHMs are assessed through a brief questionnaire and by measurement of standing height, body weight, blood glucose, blood cholesterol and blood pressure. Muscle mass is estimated from calf circumference, whereas muscle strength and function are measured via handgrip strength and chair-stand testing, respectively. Results Analyses were conducted in 6323 community-living adults (mean age: 54 ± 15 years, 57% women) recruited between 1 June 2015 and 30 June 2017. Participants presented on average 4.3 ± 1.3 ideal CHMs, which decreased with age. Only 19.5% of participants met >5 ideal metrics, while 8.3% met <3. All seven ideal metrics were met by 4.7% of enrollees. Muscle mass, strength and function declined progressively with age, starting at 45–50 years. Conclusion Our population showed suboptimal CHMs scores, with very low prevalence of all ideal metrics. The number of ideal metrics decreased progressively with age and so did muscle mass and function.